USP7 Is a Master Regulator of Genome Stability - Valles, Gabrielle J.; Bezsonova, Irina; Woodgate, Roger; Ashton, Nicholas W. (Frontiers in Cell and Developmental Biology, 2020)
Genetic alterations, including DNA mutations and chromosomal abnormalities, are primary drivers of tumor formation and cancer progression. These alterations can endow cells with a selective growth advantage, enabling cancers to evade cell death, proliferation limits, and immune checkpoints, to metastasize throughout the body. Genetic alterations occur due to failures of the genome stability pathways. In many cancers, the rate of alteration is further accelerated by the deregulation of these processes. The deubiquitinating enzyme ubiquitin specific protease 7 (USP7) has recently emerged as a key regulator of ubiquitination in the genome stability pathways. USP7 is also deregulated in many cancer types, where deviances in USP7 protein levels are corelated with cancer progression. In this work, we review the increasingly evident role of USP7 in maintaining genome stability, the links between USP7 deregulation and cancer progression, as well as the rationale of targeting USP7 in cancer therapy.